(untitled) (Journal of International Studies, 2016)
This paper examines the forces that have animated insecurity in Africa/Nigeria via the instrumentality of religious fundamentalism. Drawing data mainly from secondary sources, and leaning on social contract theoretical framework, it argues that contrary to the conventional wisdom that Boko-Harm-styled insecurity in Nigeria is fuelled by religious fundamentalism, the real force lies in neo-imperialism masquerading as globalization.To be sure, this global phenomenon though the mechanism of market reforms has further delegitimized and deconstructed the state in Africa. Put differently, it has alienated the state not only from itself but has also succeeded in alienating it from the citizens. With the alienation of the Leviathan from the society, sub-state actors step in to fill the vacuum. This is where ethnic and religious militias come into the picture.The paper submits that remediation lies in the decolonization and the restructuring of the state via the instrumentality of process-led constitution-making.